2004
DOI: 10.2214/ajr.182.2.1820427
|View full text |Cite
|
Sign up to set email alerts
|

MDCT of Acute Lower Gastrointestinal Bleeding

Abstract: MDCT is proposed as an alternative first-line investigation to locate lower gastrointestinal bleeding before placing the patient under observation or performing embolization or surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 12 publications
3
45
0
5
Order By: Relevance
“…However, CM extravasation as the only reliable sign of acute bleeding has been documented in only three patients. Tew et al [5] found lower GI bleeding sources using a 4-detector-row CT scanner in 54% of 13 patients. Miller et al [6] performed a triphasic CT imaging protocol with oral water in 19 patients and showed helical CT to identify a wide variety of causes of lower GI hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CM extravasation as the only reliable sign of acute bleeding has been documented in only three patients. Tew et al [5] found lower GI bleeding sources using a 4-detector-row CT scanner in 54% of 13 patients. Miller et al [6] performed a triphasic CT imaging protocol with oral water in 19 patients and showed helical CT to identify a wide variety of causes of lower GI hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies have suggested a good performance for the detection of sources of GI bleeding using CT. However, reports about the usefulness of CT in evaluating lower GI bleeding so far have been limited in number and scope [5][6][7][8][9], and studies on the utility of CT for the evaluation of patients with upper GI bleeding are mostly restricted to a few anecdotal reports [10,11]. In addition, CT protocols vary considerably across the different studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In our series, the bleeding site found with MDCT scan was in 100% of cases concordant with the site of bleeding identified by reference examinations, with only four patients with no extravasation identified by MDCT scan. The overall patientbased accuracy of MDCT scan in detecting acute lower GI bleeding was 88%, with use of CM extravasation as the only criterion for the presence of active bleeding and for locating the bleeding site, which is a good result compared to those from other retrospective studies (3 of 17 for Ernst et al, 33 and 7 of 13 for Tew et al 35 ) [33][34][35] and in concordance with the prospective study by Yoon et al 34 This is also higher than what was found in the recent prospective study by Zink et al 31 A note must be made that our population presented severe bleeding at the time of MDCT scan. We are in agreement with their findings of a higher accuracy of MDCT in cases of active bleeding at the time of the acquisition.…”
mentioning
confidence: 73%
“…If there are some clinical signs of GI bleeding and radiological signs of perigraft infection such as ectopic gas, periaortic fluid or soft tissue thickness > 5mm, loss of the fat pad between the intestine and the aorta, CT has an overall AEF diagnostic specificity of 100% and sensitivity of 50% (5). other hemorrhage sources that may be found using contrast enhancement CT are diverticular disease, angiodysplasia, neoplasms, pseudoaneurysms, aneurysms, colitis and arteriobiliary fistula after liver biopsy (6,7).…”
Section: Discussionmentioning
confidence: 99%